(untitled) (International Journal of Current Engineering and Technology, 2014)
A high reliability and performance can be given to mobile Ad Hoc networks with the help of efficient routing protocols. AODV (Ad hoc On-demand Distance Vector) that works dynamically to set up and sustain routes, adapting quickly to changing link conditions. AODV is an on-demand routing protocol as requested routes are made between source nodes. This paper includes the functionality and features of AODV to make it an efficient routing protocol to MANET. This paper also includes some features which can be incorporated in order to make AODV more efficient.